KHẢO SÁT SỰ HẤP THU HÓA CHẤT BẢO VỆ THỰC VẬT BỞI MnO2 VÀ ỨNG DỤNG ĐỂ XÁC ĐỊNH DƯ LƯỢNG HÓA CHẤT BẢO VỆ THỰC VẬT HỌ CHLOR TRONG MẪU NƯỚC BẰNG PHƯƠNG PHÁP GC-ECD - Lê Ngọc Chung; Nguyễn Đức Thuận (Tạp chí Khoa học Đại học Đà Lạt)
A method for the determination of organochlorine pesticides in the water samples by gas chromatography is described. The method consists of sorption of pesticides in water by Mn02 sorbent with a water: Chloroform (10:1, V/V) mixture. then the target compounds are desorbed with a acetone: n-hexane (3:1, V/V) mixture and final determination by GC-ECD. The method allows the determination of organochlorine pesticides (BHC; 4,4' DDT; 4,4' DDD; 4,4' DDE; aldrin, dieldrin, endrin, endosulfan 1, endosulfan sulfate, heptachlor, heptachlor epoxide, methoxy chlor) with relative standard deviation of 10-15%.